Quran, Sufism and Social Culture Awakening of Medieval Türkiye: The Case of Akhism - Andriawan, Didik; Alrumayh, Safa (Al-Karim: International Journal of Quranic and Islamic Studies, 2025)
Akhism, which flourished in Anatolia from the 13th to the 20th century, was a distinctive socio-economic and moral organization grounded in the ethical teachings of the Qur’an, Hadith, and Sufism. Beyond functioning as a guild for artisans, it served as a social and moral institution that fostered integrity, solidarity, and justice within the community. This study aims to examine how Qur’anic values shaped the ideological foundations and social functions of Akhism within the Ottoman context. Employing a qualitative approach with a cultural-historical focus, the research draws upon diverse sources, including historical documents, Fütüvvetnâme texts, the Qur’an, Hadith, and other records relevant to Akhism. The researcher acts as the primary instrument, applying data reduction, data display, and conclusion-drawing techniques to interpret findings. The analysis reveals that Akhism represented a dynamic synthesis of Qur’anic ethics and Sufi spirituality, operating simultaneously as a moral compass and a social regulator. This study finds that Akhism exemplifies how scriptural values can sustain social harmony, ethical discipline, and cultural resilience within medieval Turkish society. Contribution: This study contributes to understanding the embodiment of Qur’anic ethics in socio-economic structures, offering Akhism as a historical model of Islamic ethical praxis in public life.